2022
DOI: 10.1002/suco.202100915
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of hybrid fiber‐reinforced concretes made with low dosages of synthetic fibers

Abstract: Recent advances made in concrete fibers have made them one of the concrete's recommended ingredients, mainly to eliminate the drawbacks associated with the weakness of cementitious materials, such as concrete, in tension. The addition of fibers, however, introduces extra cost and labor requirements, while selecting an appropriate choice and dosage of fibers has still remained a standing question. To address the outlined issues, the current study investigates the development of fiber‐reinforced concrete (FRC) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The PP fibers were also noted to have a (relatively) high water absorption, mainly due to their porous structure. 44,45 On the other hand, the water absorption capacity of the PVA fibers was (relatively) low, i.e., in the range of 0.1%-1.0%, 46 while the water absorption capacity was even lower (i.e., to a negligible level) for AR glass and carbon fibers. A comparison of the mixtures made with synthetic fibers indicated that the workability improved from nylon to PP, carbon, PVA, and AR glass fibers.…”
Section: Flow Compressive Strength and Flexural Strength Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The PP fibers were also noted to have a (relatively) high water absorption, mainly due to their porous structure. 44,45 On the other hand, the water absorption capacity of the PVA fibers was (relatively) low, i.e., in the range of 0.1%-1.0%, 46 while the water absorption capacity was even lower (i.e., to a negligible level) for AR glass and carbon fibers. A comparison of the mixtures made with synthetic fibers indicated that the workability improved from nylon to PP, carbon, PVA, and AR glass fibers.…”
Section: Flow Compressive Strength and Flexural Strength Propertiesmentioning
confidence: 97%
“…The water absorption of nylon fibers has been reported to be as high as 3.0% (or more) by weight, 43 thus reducing the water available for achieving the desired flow. The PP fibers were also noted to have a (relatively) high water absorption, mainly due to their porous structure 44,45 . On the other hand, the water absorption capacity of the PVA fibers was (relatively) low, i.e., in the range of 0.1%–1.0%, 46 while the water absorption capacity was even lower (i.e., to a negligible level) for AR glass and carbon fibers.…”
Section: Flow Compressive Strength and Flexural Strength Propertiesmentioning
confidence: 99%
“…In the second stage (laboratory test Series 2), 24 additional prismatic specimens (20 × 90 × 400 mm) were prepared by using a constant dosage of macrofibres (12 kg/m 3 ) and varying microfiber (Crackstop ® Ultra, Adfil, Belgium) content from 0 to 3 kg/m 3 (Figure 3b). The main research question concerned the determination of whether microfibers can improve the structural toughness on the macro scale, as fairly controversial results have been reported elsewhere in the literature [23][24][25]. The results obtained from the second experimental stage are presented in Figure 3d.…”
Section: Laboratory Tests On Synthetic Fibre-reinforced Hpcmentioning
confidence: 99%
“…10 Previous studies suggested that increasing the content of steel fiber is an effective method to improve the flexural behavior of UHPCC. 11,12 However, its application is limited due to high cost of steel fibers and corrosion risk for fibers closed to the concrete surface. Consequently, seeking a method to improve the fiber utilization efficiency and the flexural property of UHPCC is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fiber content reveals a strong dependency on tensile strength 10 . Previous studies suggested that increasing the content of steel fiber is an effective method to improve the flexural behavior of UHPCC 11,12 . However, its application is limited due to high cost of steel fibers and corrosion risk for fibers closed to the concrete surface.…”
Section: Introductionmentioning
confidence: 99%